2020
DOI: 10.1002/hpja.424
|View full text |Cite
|
Sign up to set email alerts
|

Dementia knowledge, art, research and education – Teaching primary school children about dementia

Abstract: Dementia is an umbrella term for a group of diseases that cause progressive cognitive impairment, including impact on memory, intellect, rationality, social skills and physical functioning. 1 Dementia can occur at any age, but it is more common after the age of 65. 1 For a number of years the rates of dementia have been increasing in the population. [2][3][4] This is of concern as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Both the quantitative data collected from a pre‐post survey and analysis of the students' artworks showed that participation in Project Dare increased students' understanding and knowledge of dementia 8,9 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both the quantitative data collected from a pre‐post survey and analysis of the students' artworks showed that participation in Project Dare increased students' understanding and knowledge of dementia 8,9 …”
Section: Methodsmentioning
confidence: 99%
“…In Lesson 1, the students created an artwork about memory, in Lesson 2 they learned about dementia and in their final lesson they adapted their artwork to represent their developing understanding of dementia. 8,9 During the art lessons, artists demonstrated the use of techniques to express emotions and experiences.…”
Section: Study Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Impact : A mixed‐method evaluation was carried for children, parents and community members 25‐27 . Understanding of dementia and its impressions improved from this short intervention as indicated by improvement scores in the Kids Insight into Dementia Survey scale and contrasts between ‘before’ and ‘after’ artworks.…”
Section: Artful Elements and Their Impactsmentioning
confidence: 99%